Bamboo (betung species) fiber composite plate for external strengthening of RC beams - Moh Neing Sheng, Jacky (2018)
Natural fibers are being introduced to replace the synthetic fiber in the manufacturing of fiber composites due to its environmental friendly behavior. A research had been conducted to investigate the mechanical properties of bamboo (Betung species) and its potential to be used as bamboo fiber composite plate (BFCP) for the external strengthening of reinforced concrete (RC) beams. Raw bamboo culms were obtained from Raub, Pahang. Mechanical behaviour of raw and dried bamboo specimens was tested under compression test and tension test. All the BFCPs with 0.4 fiber-to-volume ratio have been fabricated and tested for flexural test (ASTM D790-03) and tensile test (ASTM D3039) to determine the mechanical properties. Four-point loading test was conducted to study the behaviour of reinforced concrete (RC) beam under external strengthening effect with BFCP. The result showed that bamboo of Betung species has a density of 0.807 g/cm3. In compression test, bamboo culms fail in two modes: fiber cracking and fiber crushing. Dried bamboo specimens recorded 19.5 % higher in compression strength than raw bamboo specimens. There was an improvement of 45 % of average tensile strength in raw bamboo samples compared to dried specimens. In terms of mechanical behaviour, BFCP has higher flexural and tensile strength than pure epoxy samples where the flexural and tensile strength of BFCP increased by 666 % and 178 % respectively. The interfacial adhesion between the bamboo fiber and epoxy resin in BFCP greatly improved the structural bonding and mechanical properties. From the four-point loading test, BFCP strengthened beams had achieved the total load bearing capacity of 96 % and 97 % compared to solid control beam. Compared with un-strengthened beam, the load bearing capacity of BFCP strengthened beam increased by 10 % and 12 %. Installation of BFCP manage to divert the vertical cracks at the tension zone to the edge of the plate forming diagonal cracks. This proved that BFCP has potential to be used as external strengthening material in RC beams.